Case Report: Fascioliasis Hepatica Precisely Diagnosed by Metagenomic Next-Generation Sequencing and Treated With Albendazole - Zhang, Yaling; Xu, Huan; Liu, Yi; Kang, Juan; Chen, Hairu; Wang, Zhiyi; Cai, Dachuan (Frontiers in Medicine, 2021)
The clinical manifestations of fascioliasis hepatica in humans are unspecific. Traditional diagnosis relies on evidence of live parasites or eggs in the bile or feces. However, due to similar imaging manifestations, they are often misdiagnosed as malignant tumor. Here, we report a case of a 43-year-old woman with fever and space-occupying liver disease. Liver biopsy, parasite-specific antibody screening, and stool testing did not find any pathogens. Therefore, metagenomic next-generation sequencing (mNGS) and routine microbiological examinations were performed. Finally, Fasciola hepatica was only identified by mNGS. Patient's body temperature and the eosinophil count remained normal, and the space-occupying liver lesions were significantly absorbed after more than seven months of treatment with albendazole. The details of this case highlight the timely use of metagenomic NGS to identify parasite and judge therapeutic effect after treatment, providing important help for clinical decision-making.